1979
DOI: 10.1055/s-0038-1657063
|View full text |Cite
|
Sign up to set email alerts
|

Relative Activities of Heparin Fractions Obtained by Gel Chromatography

Abstract: SummaryIn order to investigate the reported heterogeneity of commercial heparin injections, lung and mucous preparations were fractionated by gel chromatography according to molecular size. Eluent pools were characterized by measuring electrophoretic mobility, anticoagulant activity using a reactivation assay and an anti-Xa assay, lipolytic activity and the protamine neutralization value. The only biological activity to show a marked relationship with the molecular size of the heparin fraction was the anti-Xa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…These molecular components exert specific pharmacologic actions by interacting with various endogenous proteins, thereby collectively producing an antithrombotic effect. 12,15,16,[18][19][20][21]27,36 It has been suggested that the primary antithrombotic actions of heparin are determined by molecular fractions that exhibit strong affinity for antithrombin III and in a complex form with this plasma cofactor produce potent antiprotease actions. 7,8a,10,11,22,35 It has also been proposed that low-affinity heparin fractions produce a modulatory action on the pharmacologic activity of high-affinity fragments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These molecular components exert specific pharmacologic actions by interacting with various endogenous proteins, thereby collectively producing an antithrombotic effect. 12,15,16,[18][19][20][21]27,36 It has been suggested that the primary antithrombotic actions of heparin are determined by molecular fractions that exhibit strong affinity for antithrombin III and in a complex form with this plasma cofactor produce potent antiprotease actions. 7,8a,10,11,22,35 It has also been proposed that low-affinity heparin fractions produce a modulatory action on the pharmacologic activity of high-affinity fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing newer separation techniques, heparin can be fractionated into various molecularly defined species possessing specific, individual biochemical and pharmacologic actions. 7,11,12,20,23,26 Furthermore, based on structural information, oligosaccharide fragments with high affinity to antithrombin III can be obtained by various physicochemical methods. 10,11,28,31,37 Moreover, it is now possible to study completely synthetic oligosaccharides, of which pentasaccharide represents the first molecularly defined biologically active fragment of heparin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,52 Experiments by academic and commercial investigators rapidly exploited this new field, reporting on newer methods of fractionation, relationships between molecular weight and antithrombin activity, and the ratio of factor Xa to IIa activity. [53][54][55] Fractionation methods are listed in Table 1.…”
Section: Era Of Rapid Expansion 1977 To 2003mentioning
confidence: 99%
“…They have varying affinities to antithrombin III (AT III) and exhibit inhibitory effects on serine proteases. 9,14,[16][17][18] Heparin and several heparin fractions have been studied in multiple in vitro and ex vivo test systems to demonstrate the utility of various serine proteases and global coagulant and synthetic substrate-based assays.…”
mentioning
confidence: 99%